Pengaruh Kualitas Air Terhadap Produktivitas Lobster Bambu (Panulirus Versicolor) dengan Sistem Keramba Jaring Apung di Perairan Teluk Sinabang Kabupaten Simeulue - Nelvia Mai Susanti; Rahmat Tillah; Irmayadi Sastra; Mira Rahmita Sari (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to analyze the effect of water quality on the productivity of bamboo lobsters (Panulirus versicolor) cultivated in a floating net cage sistem (KJA) in the waters of Sinabang Bay, Simeulue Regency. Water quality is one of the main environmental factors that determines the success of marine cultivation, especially for high-value species such as bamboo lobsters. Water quality parameters observed in this study included temperature, salinity, pH, dissolved oxygen (DO), and ammonia levels. Measurements were carried out periodically during the 90-day cultivation period to capture environmental dynamics that affect the biological performance of lobsters. This study used a Completely Randomized Design (CRD) experimental design with three treatments based on different cultivation locations that have variations in natural water quality, each with three replications. The results showed that optimal water quality significantly affected the increase in bamboo lobster productivity, as indicated by the parameters of the specific growth rate (SGR), feed conversion efficiency (FCR), and survival rate (SR). The location with the best water quality (P1), which had high DO and low ammonia levels, recorded a daily SGR of 1.82%, a FCR of 1.6, and a SR of 90%. Conversely, the location with low water quality (P3) showed significantly decreased biological performance, with suboptimal SGR, FCR, and SR, primarily due to low dissolved oxygen and high levels of toxic ammonia. These findings emphasize the importance of continuous monitoring and management of water quality in marine cage sistems to support optimal lobster growth and survival. Therefore, managing aquatic environmental quality is key to increasing mariculture productivity and ensuring the sustainability of fishery resources in coastal areas.